1980
DOI: 10.4319/lo.1980.25.2.0248
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and coccolith formation: Inorganic carbon sources and net inorganic reaction of deposition1

Abstract: The concept that the formation of CaCO3 coccoliths functions as a photosynthetic adaptation for the use of bicarbonate is evaluated in the coccolithophorids Coccolithus huxleyi and Cricosphaera carterae by two new methods. In the first, carbon fixation is measured at 10‐s intervals in the first 2 min after addition of 14CO2 and H14CO3− to buffered cultures; this method exploits the relatively long half‐time for the hydration or dehydration of dissolved CO2. In the second, shifts in pH and alkalinity resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(117 citation statements)
references
References 24 publications
5
110
2
Order By: Relevance
“…There is experimental evidence that HCO − 3 is the principal inorganic carbon source utilised for calcification (Sikes et al, 1980;Buitenhuis et al, 1999). The dependence of calcification on HCO ] makes this ion a key candidate responsible for at least some of the pronounced increase in DSA, DSL, and DSW observed within that range ( Fig.…”
Section: Influence Of Individual Carbonate Chemistry Parameters On Comentioning
confidence: 99%
“…There is experimental evidence that HCO − 3 is the principal inorganic carbon source utilised for calcification (Sikes et al, 1980;Buitenhuis et al, 1999). The dependence of calcification on HCO ] makes this ion a key candidate responsible for at least some of the pronounced increase in DSA, DSL, and DSW observed within that range ( Fig.…”
Section: Influence Of Individual Carbonate Chemistry Parameters On Comentioning
confidence: 99%
“…In addition to their role as primary producers, coccolithophores play a predominant function in global ocean calcification (Rost and Riebesell, 2004), accounting for up to half of the share (Milliman, 1993). While still is under debate, calcification in coccolithophores appears to be strongly linked to photosynthesis by favoring supply of CO 2 (Anning et al, 1996;Sikes et al, 1980;Sikes and Wilbur, 1982); moreover, Nimer et al (1996) found reduced photosynthetic rates when removing external calcium. Other studies (Herfort et al, 2002(Herfort et al, , 2004Trimborn et al, 2007;Leonardos et al, 2009) however, showed that changes in calcification under altered Ca 2+ concentrations did not bring about concomitant changes in photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Coccolithophores fix CO 2 into organic matter by photosynthesis, contributing to the drawdown of atmospheric CO 2 (Raven and Falkowski, 1999). Calcification, on the other hand, releases CO 2 in the short term (Rost and Riebesell, 2004) and stores carbon in coccoliths in the long term (Sikes et al, 1980;Westbroek et al, 1993). In addition, coccolith ballast can accelerate the removal of organic carbon from upper water layers and aid long-term burial of carbon (Ziveri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%